Reliability and validity of the patient disability-oriented diagnostic nomenclature system for prosthetic dentistry. Issue 1 (January 2017) - Matsuka, Yoshizo; Hagiwara, Yoshiyuki; Tamaki, Katsushi; Takeuchi, Hisahiro; Fujisawa, Masanori; Ono, Takahiro; Tsukiyama, Yoshihiro; Nagao, Kan; Tsuga, Kazuhiro; Aita, Hideki; Kondo, Hisatomo; Fueki, Kenji; et al.
Abstract: Purpose: The Japan Prosthodontic Society (JPS) has proposed a new diagnostic nomenclature system (DNS), based on pathogenesis and etiology, to facilitate and improve prosthodontic treatment. This system specifies patient disability and the causative factor (i.e. " B (disability) caused by A (causative factor)"). The purpose of this study was to examine the reliability and validity of this DNS. Study selection: The JPS Clinical Guideline Committee assessed mock patient charts and formulated disease names using the new DNS. Fifty validators, comprising prosthodontic specialists and dental residents, made diagnoses using the same patient charts. Reliability was evaluated as the consistency of the disease names among the validators, and validity was evaluated using the concordance rate of the disease names with the reference disease names. Results: Krippendorff's α was 0.378 among all validators, 0.370 among prosthodontic specialists, and 0.401 among dental hospital residents. Krippendorff's α for 10 validators (3 specialists and 7 residents) with higher concordance rates was 0.524. Two validators (1 specialist and 1 resident) with the highest concordance rates had a Krippendorff's α of 0.648. Common disease names had higher concordance rates, while uncommon disease names showed lower concordance rates. These rates did not show correlation with clinical experience of the validator or time taken to devise the disease name. Conclusions: High reliability was not found among all validators; however, validators with higher concordance rates showed better reliability. Furthermore, common disease names had higher concordance rates. These findings indicate that the new DNS for prosthodontic dentistry exhibits clinically acceptable reliability and validity.